AJUSTE GENITAL EN LA COPULA DE THYNNINAE (HYMENOPTERA, TIPHIIDAE) - Toro, H.; Carvajal, C. (Acta Entomológica Chilena, 2022)
Aspeas of che mechanics of phorectic copulation of Eiaph roptrra unlmejormis (Halidav) are described. Various parts of the complex aedeagus. che eight meiasomal slernum of the male and ihe teníale copulatory pouch, make the locking mechanism possible. When protruding, the eight slernum roíales and push the male genitalia into the female. The copulatory pouch is formed by protrusion of the last stemum of the female, il has a ventral space for the aedeagus. lateral pouches for the flap-like aedeagal struaures and a dorsal sclerotized bar for the articulated penis valvae.